Edukasi Lembaga Keuangan Bank dan Non-Bank pada SMK Swasta PAB 12 Saentis - Putri Nazli; Siti Kadariah; Mutia Indriani (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
The development of the sharia financial system is marked by the establishment of various sharia institutions and the issuance of various sharia-based financial instruments. One of the most prominent institutions is sharia banks, which not only serve as financial intermediaries that collect and distribute funds to the community but also provide various services, including pawning. Bank Syariah Indonesia is one of the leading banks offering a gold pawn product, which has been considered successful due to its continuous growth every year. Sharia gold pawn financing is a product that channels funds in the form of loans, based on the qard principle, where gold serves as collateral for the customer’s money. The process involves several stages that must be followed by both the bank and the customer. Bank Syariah Indonesia has managed to set relatively low rental fees for its gold pawn products compared to other financial institutions, making it an attractive option for customers in need of short-term financing. In this community service activity, the aim is to provide a detailed explanation of the mechanism behind the gold pawning product at Bank Syariah Indonesia. By doing so, the public is expected to become more familiar with the services, operations, and benefits offered by sharia banks, particularly in the context of gold pawn financing. This initiative aims to increase the understanding and awareness of the public about the advantages of using sharia-based financial products, as well as highlight the role of such services in supporting the financial needs of individuals while adhering to Islamic principles. Through this outreach, it is hoped that more people will consider utilizing these financial services, thus contributing to the broader development of sharia finance